Upaya Guru PAI dalam Meningkatkan Minat Belajar Baca Tulis Al Qur’an di SMAN 1 Juwana Pati - Kamto, Kamto (AL-BURHAN, 2023)
This study aims to determine the efforts of Islamic Religious Education teachers in increasing interest in learning to read and write the Qur'an at SMAN 1 Juwana and to determine the supporting and inhibiting faktors. The type of research is a case study with a descriptive qualitative approach. The primary sources are Islamic Religious Education teachers and students, while secondary data are literature studies and supporting documents. Data collection techniques are in-depth interviews, observations, and document studies. Analysis techniques are data reduction, data presentation, and conclusions or data verification. The results of the study show that the efforts made by Islamic Religious Education teachers in increasing interest in learning to read and write the Qur'an at SMAN 1 Juwana are by taking a personal approach, conducting learning activities to read and write the Qur'an with a variety of learning methods, using existing technology such as LCD projectors, Al-Qur'an reading and writing applications, and other supporting technologies as well as applications such as